Learning Vocabulary through Didactic Games - Strnadová, Lucie (Univerzita Pardubice, 2018)
The topic of the bachelor thesis is learning vocabulary through didactic games. The theoretical part begins with a look into the primary learners who are described from the point of view of psychological development, language learning, and second language education. Secondly, there is described vocabulary learning with all its aspects. Then the thesis focuses on didactic games, especially on the definition, types of didactic games, and their use in the classroom environment. The thesis then identifies the didactic principles regulating the process of teaching and learning. The practical part includes a set of eight didactic games designed for primary learners to learn English vocabulary.
Osvojování slovní zásoby prostřednictvím didaktických her
Keywords: slovní zásoba; didaktické hry; učení; žáci prvního stupně základní školy; vocabulary; didactic games; learning; primary learners